La trame verte et bleue et ses réseaux : science, acteurs et territoires - Pierre Alphandéry; Agnès Fortier (VertigO)
The bill to set up the French ecological network called “Trame verte et bleue (TVB) “was passed in 2007 at the end of debates which characterised the process of Grenelle de l’Environnement. The outcome has renewed the approach of biodiversity policy as it was envisioned in a logic of land management. Its goal is to balance the fragmentation of space and natural habitats caused by human activities by the means of restoring connections in order to make possible the movement of species and genes. Our sociological work highlights the place of TVB in French nature policy and focuses on how ecological and teritorial aspects are linked. Starting from the analysis of the TVB system viewed as a government tool (in the manner of Michel Foucault) we point out how prescriptive the scheme is on the regional and national scales, in the name of scientific relevance, while giving a large autonomy to local authorities in the process of implementing the TVB. Beyond the consensus of the Grenelle de l’environnement, this mixture of prescription and autonomy, which partly explains the complexity of the scheme, makes possible different ways of looking at the TVB. In the end, the implementation process of the TVB raises the issue of the way ecology is applied in territory projects and symmetrically, the way social groups and institutions appropriate the TVB project.